ZnO Quantum Dots Induced Oxidative Stress and Apoptosis in HeLa and HEK-293T Cell Lines - Yang, Yanjie; Song, Zhenhua; Wu, Weixia; Xu, Ao; Lv, Shuangyu; Ji, Shaoping (Frontiers in Pharmacology, 2020)
Zinc oxide (ZnO) quantum dot (QD) is a promising inexpensive inorganic nanomaterials, of which potential toxic effects on biological systems and human health should be evaluated before biomedical application. In this study, the cytotoxicity of ZnO QDs was assessed using HeLa cervical cancer cell and HEK-293T human embryonic kidney cell lines. Cell viability was significantly decreased by treatment with 50 µg/mL ZnO QDs after only 6 h, and the cytotoxicity of ZnO QDs was higher in HEK-293T than in HeLa cells. ZnO QDs increased the level of reactive oxygen species and decreased the mitochondria membrane potential in a dose-dependent manner. Several gene expression involved in apoptosis was regulated by ZnO QDs, including bcl-2 gene and caspase. In HeLa cells, ZnO QDs significantly increased early and late apoptosis, but only late apoptosis was affected in HEK-293T cells. These findings will be helpful for future research and application of ZnO QDs in biomedicine.